Pengaruh Perceived Quality Experience, Perceived Value Experience, dan Aesthetic Experience terhadap Revisit Intention melalui Tourist Satisfaction Wisatawan Carita Alam - Suryani Taufik, Dena; Yadi Ernawadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of perceived quality experience, perceived value experience, and aesthetic experience on revisit intention, mediated by tourist satisfaction among tourists visiting Carita Alam. Based on low Google Maps ratings, this study identifies factors that can increase tourist satisfaction and revisit intention. Data were collected through a survey of 125 respondents using a purposive sampling technique and analyzed using SmartPLS 3.0. The results indicate that perceived value experience and aesthetic experience significantly influence tourist satisfaction, while perceived quality experience has no significant effect. Tourist satisfaction proved to have the strongest influence on revisit intention and mediated the influence of value and aesthetic experience. These findings strengthen Expectation Confirmation Theory (ECT) and Experience Economy Theory (EET) in explaining the importance of valuable and aesthetic experiences in shaping satisfaction and loyalty among tourists visiting Carita Alam. Keywords: Perceived Quality Experience, Perceived Value Experience, Aesthetic Experience